2014
DOI: 10.1002/hup.2395
|View full text |Cite
|
Sign up to set email alerts
|

A single‐dose, randomized, double‐blind, double dummy, placebo and positive‐controlled, five‐way cross‐over study to assess the pharmacodynamic effects of lorediplon in a phase advance model of insomnia in healthy Caucasian adult male subjects

Abstract: Lorediplon demonstrated a dose-dependent improvement in sleep, whereas zolpidem showed a more sustained WASO effect. No next-day hangover effects were observed. These sleep effects are also consistent with the pharmacokinetic profile of lorediplon. These results warrant clinical trials in patients with insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Following single-dose administration, a dose-related awakening effect was observed, consistent with the pharmacology of H 3 R antagonists (Horoszok et al, 2014; Krystal et al, 2011; Mehta et al, 2001; Mehta et al, 2004). The sensitivity of WASO, however, appeared to decrease approximately 10-fold after multiple dosing.…”
Section: Discussionsupporting
confidence: 71%
“…Following single-dose administration, a dose-related awakening effect was observed, consistent with the pharmacology of H 3 R antagonists (Horoszok et al, 2014; Krystal et al, 2011; Mehta et al, 2001; Mehta et al, 2004). The sensitivity of WASO, however, appeared to decrease approximately 10-fold after multiple dosing.…”
Section: Discussionsupporting
confidence: 71%
“…143 Lorediplon A phase I study of the pharmacodynamics of lorediplon showed that it decreased WASO and increased total sleep time. 144 In a comparison with both placebo and zolpidem, lorediplon showed similar results to zolpidem. A randomized, phase II double blind, placebo controlled crossover study to evaluate the dosage needed and the drug's efficacy in sleep maintenance and sleep onset as well as its adverse effect profile began in 2014.…”
Section: Skp-1041mentioning
confidence: 87%
“…1 Particularly, some synthetic purine analogues containing pyrazolo [1,5-a]pyrimidine nucleus have received augmented interest in recent years due to their broad range of applications in medicinal chemistry and drug design. 2 For instance, the anxiolytic agent ocinaplon, 3 and the hypnotic drugs indiplon, 4 lorediplon, 5 and zaleplon, 6 among others potential drugs 7 have this structural motif of pyrazolo [1,5-a]pyrimidine (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%